G487(P) Is clinician gaze and body language associated with their ability to identify safeguarding cues?. (25th October 2020) - Powell, A; Collingwoode-Williams, T; Schindler, N; Pan, SX; Fertleman, C
Abstract : Aims: Do GPs who undertake a covert child safeguarding virtual reality scenario use empathetic body language and look at the child in a parental consultation? Methods: This study used virtual reality consultations from 'A study of professional awareness using virtual reality: the responsiveness of GPs to child safeguarding cues' . These detail a consultation between a GP and a virtual reality avatar of a father and son. The behaviour of the father towards his son should elicit concern. This study investigated whether the body language and gaze behaviour of the clinician was associated with their ability to identify safeguarding cues. Body language was measured in terms of head nod, body lean and eye contact, and gaze as the proportion of the consultation in which the clinician was looking at the child. We conducted follow-up interviews with GP participants 18 months after the original study. These interviews covered their opinions of the study and virtual reality in general. Consultations from 61 original participants were used, and 12 were interviewed. Results: There was a strong, statistically significant association (δ = 0.606, p < 0.05) between empathetic body language and an ability to identify safeguarding cues. There was a weak, non-significant association ( τ b = 0.202, p= 0.06) between child-directed gaze and an ability to identify safeguarding cues. At follow-up interview, some GPs felt that virtual reality was a useful training tool as it was more accessible than traditional training with actors. There was a consensus that the current iteration of the interface was not reactive enough, and that this was a barrier to interaction with the avatar and immersion in the consultation. Conclusion: This study has shown an association between empathetic body language and an ability to identify safeguarding cues within a simulated virtual reality consultation. Future prospective research could help determine why this association exists and if teaching in non-verbal communication skills can help to improve the recognition of safeguarding cues in clinical practice. It has also highlighted the use of virtual reality in paediatric safeguarding training, where child actors cannot be used, due to their age and the sensitivity of the scenario.